Usual medical treatments or levonorgestrel-IUS for women with heavy menstrual bleeding: long-term ranomised pragmatic trial in primary care - Kai, Joe; Middleton, Lee; Daniels, Jane; Pattison, Helen; Tryposkiadis, Konstantinos; Gupta, Janesh (Royal College of General Practitioners, 2016)
Background: Heavy menstrual bleeding (HMB) is a common, chronic problem burdening women and health services. However long-term evidence on treatment in primary care is lacking.